ANALISIS KAIDAH KEBAHASAAN DALAM NOVEL SESUAP RASA KARYA CATZ LINK TRISTAN SEBAGAI ALTERNATIF PEMILIHAN BAHAN AJAR BAHASA INDONESIA KELAS XII - Asti Pujiastuti Hidayat; Titin Nurhayatin; Adi Rustandi (STKIP Subang, 2022)
Learning about novels is an important lesson that must be mastered by students. However, in reality, students find it difficult to analyze novels because of a lack of understanding of the material. One of the reasons is the selection of Indonesian language teaching materials that are less attractive. Therefore, the author researched the linguistic rules of the novel so that it can be used as alternative teaching material. This study aims to analyze the linguistic rules in the novel Sesuap Rasa by Catz Link Tristan as a choice of Indonesian language teaching materials for class XII. The research method used is qualitative with data collection techniques, namely documentation, and literature study. The author uses data sources in the form of 61.53% of the number of pages in the novel. The results of the analysis show that 61.53% of the number of pages in the novel Sesuap Rasa by Catz Link Tristan contains 6 novel linguistic rules consisting of 471 adverbs of time, 1122 personal pronouns, 591 material verbs, 470 mental verbs, 517 adjectives. , and 979 dialogues. Based on the results of the study, the linguistic rules of the novel that have been analyzed can be used as teaching materials by the demands of the 2013 Curriculum. The results of the validation of Indonesian class XII teaching materials in the form of modules obtained an overall average score of 4.61 with a percentage of 92.2% included in the